Temporal-Comparative Feedback Facilitates Golf Putting - Chiviacowsky, Suzete; Harter, Natália Maass; Gonçalves, Gisele Severo; Cardozo, Priscila Lopes (Frontiers in Psychology, 2019)
The present experiment investigated the influence of temporal-comparative feedback in young adults learning a sport motor skill. A positive temporal-comparative feedback group and a control group practiced putting golf balls to a target from a distance of 150 cm and received augmented feedback (deviation in cm) in addition to their intrinsic visual feedback. The temporal-comparative feedback group was given additional feedback after each block of 10 trials, suggesting that their average performance was better than it was in the previous block. One day after the practice phase a retention test was performed, to observe learning effects. The results showed that positive temporal-comparative feedback enhances the learning of a putting golf task. Greater putting accuracy was observed on the retention test for the temporal comparison group relative to the control group. Questionnaire results also indicated that participants in this group reported higher perceived competence at the end of practice relative to control participants. The findings provide further indication that temporal comparison affects the learning of motor skills and highlight the important motivational role of feedback in motor learning.